Comparative analysis of radio propagation models for LTE network on the sky train - Dataesatu, Arif; Boonsrimuang, Pornpawit; Mori, Kazuo; Boonsrimuang, Pisit (My University, 2019)
The usage of smartphones and computer for the data communications have become a more integrated part of everyday life for a large majority of the population. One important mode of transportation is the sky train, and users increasingly expect to be able to communicate satisfyingly while traveling on the train: MRT (Mass Rapid Transit Authority of Thailand). However, the radio conditions inside a train are very complex. A possibly large number of users that use at the same time, moving at high speed and a special environment on elevated guideways (height 20 m) are created big challenges for the data communication in LTE network. The accuracy of the path loss model is a very important tool to design the coverage areas and improve the performance in LTE network. This paper that studies and improve the accuracy of the path loss model, which use to design the coverage area of the LTE network under the sky train environment. Normally the radio propagation models under the urban area are designed on the ground approximately 1-3 meters in height but are not suitable for the user in the sky train, which is 20 meters high. we propose the Ericsson urban model in the special environment as sky train by the new values for a0 from 36.2 to 47.2 and a1 from 30.2 to 14.2. The proposed new coefficient for Ericsson urban model shows the most accurate path loss under the sky train with the urban area. The filed measurement is used by the smartphone-based measurement for low cost and practical usage.
Keywords: Ericsson model and Sky train MRT; LTE; Path loss